How parent-child problematic internet use affect procrastination among adolescents: A review of theoretical framework and empirical evidence - Anis Aniza, Awi; Puteri Fadzline, Muhamad Tamyez (Asian Scholars Network (ASNet), 2020)
The web is a technology which has become a huge part of people's day lives from adults as well as adolescents. Since decades ago, online connectivity has developed tremendously and it is available all over places including homes, offices, schools and travels. Nowadays, empirical studies report that adolescents with a strong tendency to be procrastination in which irrational task delay, especially susceptible to utilize Internet uses concurrently to various other responsibilities (e.g., during homework) due to insufficiently controlled way. The insufficiently controlled of internet use might be due to the bad brain health implications which the users have often been connected until become procrastination. The current study explored the significant evidence relating to Parent-Child PIU that impact to adolescent and procrastination including theoretical framework. The study also underlines adolescents with high levels of procrastination might have a heightened risk for bad outcomes that leads to insufficiently controlled the use of Internet.